2013
DOI: 10.3409/fb61_3-4.165
|View full text |Cite
|
Sign up to set email alerts
|

DNA Methylation Analysis of the Gene CDKN2B in Gallus gallus (Chicken)

Abstract: GRYZIÑSKA M., ANDRASZEK K., G. JOCEK. 2013. DNA methylation analysis of the gene CDKN2B in Gallus gallus (chicken). Folia Biologica (Kraków) 61: 165-171.Methylation is an epigenetic modification of DNA affecting gene expression without changing the structure of nucleotides. It plays a crucial role in the embryonic and post-embryonic development of living organisms. Methylation level is tissue and species-specific and changes with age. The study was aimed at identifying the methylation of the CDKN2B gene situat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 13 publications
(9 citation statements)
references
References 29 publications
(34 reference statements)
0
9
0
Order By: Relevance
“…Methylation-specific PCR (MSP) and sequencing of amplified DNA fragments following the use of sodium bisulfite and PCR (BSP) are considered to be among the most effective techniques for detecting methylated genes [23]. Both methods exploit cytosine deamination (conversion into uracil) in single-stranded DNA [24,25]. Moreover, both methods are highly sensitive -analysis requires about 200 pg of genomic DNA, which corresponds to about 100 cells [26].…”
Section: Discussionmentioning
confidence: 99%
“…Methylation-specific PCR (MSP) and sequencing of amplified DNA fragments following the use of sodium bisulfite and PCR (BSP) are considered to be among the most effective techniques for detecting methylated genes [23]. Both methods exploit cytosine deamination (conversion into uracil) in single-stranded DNA [24,25]. Moreover, both methods are highly sensitive -analysis requires about 200 pg of genomic DNA, which corresponds to about 100 cells [26].…”
Section: Discussionmentioning
confidence: 99%
“…If the user selects primers with predicted CpG islands as a destination region, they should follow a set of rules reflecting the number and size of CpG islands found (GRYZINSKA & al. [20]; LI & DAHIYA [24]).…”
Section: Design Of Primersmentioning
confidence: 98%
“…The most commonly used method is MS-PCR (GRYZINSKA & al. [20]). The MSP (methylation-specific PCR) reaction was first described in 1996 by HERMAN & al.…”
Section: Design Of Primersmentioning
confidence: 99%
“…More precisely, IBD may be caused by interactions between the host and the environment, which involve intestinal microflora, the immune system, and genetic determinants. Research has shown that the structure of the host organism and specific environmental factors, such as cigarette smoking, drug use, breastfeeding and diet, enter into interactions via epigenetic mechanisms, or more precisely DNA methylation (6,24).…”
Section: Other Risk Factors For Tumour Development In Ibdmentioning
confidence: 99%